Edukasi kesehatan tentang penyakit anemia dalam keluarga - Risa Lutfiatul Rohimah; neng wiwin m; nur ash shafa; rini fitriani; riza nuraeni putri (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Introduction : Anemia is a disease where there is a lack of that function red blood cells to distribute the body oxygen throughout, but in practice it cannot be fulfilled properly. Lack of energy intake, iron, protein intake, and vitamin C intake are some of the factors that cause anemia. Usually people who have anemia have low physical endurance, difficulty concentrating, and decrease physical activity caused by insufficient blood binding and air or oxygen transport flowing from the lungs to all members of the lungs. Anemia symptoms in general are weak, signs of a hyperdynamic state (strong and rapid pulse, palpitations, and sound disturbance in the ear). Many factors can cause anemia, namely iron deficiency, namely increased needs, iron deficiency, infectional bleeding and other factors. Women are more susceptible to anemia than men because women experience menstruation every month and adult women, especially those who are married, will experience pregnancy, require three times as much red blood cells as usual. Objective : Counseling was carried out to families that aimed to provide prevention education against anemia. Method : This education prevention is carried out by the observation method where materials are presented through brochures and power points. Result : After delivering the material, then a question and answer session and evaluation were to find out how far the family understanding of the material has been delivered. Conclusion : In accordance with the evaluation results, health promotion activities with anemia prevention counseling counseling group, namely timeliness, participation, and problem solving.